Discectomy without replacement improves function in patients with internal derangement of the temporomandibular joint. Issue 9 (September 2017) - Miloro, Michael; McKnight, Matthew; Han, Michael D.; Markiewicz, Michael R.
Abstract: Purpose: Treatment of internal derangement is controversial. This study assessed the effectiveness of discectomy without replacement in improving jaw function and decreasing pain. Materials and methods: A retrospective cohort study sample of subjects with internal derangement underwent discectomy without replacement by one surgeon at a single academic medical center. The primary predictor variables were preoperative maximal incisal opening (MIO) and Helkimo Clinical Dysfunction Index (CDI) score. The primary outcome variable was postoperative MIO and CDI score. A paired student's t -test assessed the difference between pre- and post-operative MIO and CDI scores. Results: Preoperatively, all patients had a clinical dysfunction index of DiIII, indicating severe dysfunction. Postoperatively 14 of 17 subjects (82%) showed marked improvement in mandibular function, and reduction in pain characterized as clinically symptom-free or only small dysfunction (DiO or DiI). One subject improved to DiII and two remained DiIII due to poor compliance. Preoperatively all subjects had an anamnestic index of AiII, representing TMJ locking or severe TMJ or muscle pain. Postoperatively 15 of 17 patients (88%) improved to AiO or AiI, and the two patients with poor compliance remained at AiII, but with marked pain reduction. Of the 17 subjects, the mean pre- and post-operative MIO was 24.2 mm and 34.9 mm, respectively (p < 0.001). There was a significant difference in pre- and post-operative MIO in subjects with Wilkes III (p = 0.005) and Wilkes IV (p = 0.008), but not Wilkes V (p = 0.7). Mean pre- and post-CDI scores were 17.3 and 3.8, respectively (p < 0.001). When stratifying by Wilkes stage, there was a significant difference in pre- and post-operative CDI in subjects with Wilkes III (p < 0.001) and Wilkes IV (p < 0.001), but not Wilkes V (p = 0.1). Conclusions: In Wilkes III and IV subjects, discectomy without replacement is effective in improving MIO based upon improvement in objective and subjective assessments.